BENTENG BALANGNIPA DI KABUPATEN SINJAI, SULAWESI SELATAN (POLA TATA RUANG DAN ARTI PENTING KEDUDUKANNYA) - Sarjiyanto (Berkala Arkeologi, 2002)
The fort complex was not very large, so there were only a few simple main buildings. This is related to the function, level of space requirements and the role of the fort. The internal condition of the Netherlands is also experiencing a decline in strength and threats from outside at that time. The artifactual remains also show the role (of the Dutch) in the use of the fort. The construction of the fort considered economic interests by trying to control the kingdom of Bone and the strategic bay of Bone. Fort Balangnipa was once used for Indonesian independence fighters, police dormitories, and currently planned to be use as a regional museum. This fort proved to be of real importance especially for the Sinjai area and for the Dutch when they wanted to control Bone because of their economic interests. The remains of the existing colonial fortress also enriched the historical data of the Indonesian struggle, especially the Bone kingdom.